Wer fährt eigentlich wie viel? Volumen und Struktur der Fahrleistung deutscher Kraftfahrzeuge 1993/2002. - Hautzinger, Heinz; Stock, Wilfried (Deutscher Verkehrs-Verlag, 2005)
Mit der Fahrleistungserhebung 2002 wurden erstmals wieder seit 1993 für alle Kfz-Arten empirisch breit abgesicherte Fahrleistungsdaten bereitgestellt. Die Daten sind unter anderem für die anhaltende Diskussion um Stagnation oder gar Rückgang der Verkehrsnachfrage relevant. Der Beitrag fasst die Ergebnisse dieses bedeutenden Vorhabens der Verkehrsstatistik zusammen. difu

According to the 2002 mileage survey, the 53.5 million vehicles registered in Germany in that year covered 703 thousand million kilometers within and outside Germany, an increase of 11.4 % over the results of 1993. The most notable increases recorded were for tractors (+75.2 %) while it was + 9.1 % for private cars. Out of the total result for 2002, the private passenger cars' share stood at 85 %; for heavy goods vehicles and tractors, the share amounted to 11 %. Since the fleet of vehicles got bigger by 17.9 % from 1993 until 2002, indications are that the average annual mileage decreased by 6.8 %. In 2002, German-registered vehicles have, on average, covered about 13500 km each per year. A differentiation according to the type of vehicle shows that tractors have achieved the highest average mileage (73700 km), while small motor-assisted bicycles and mopeds have the lowest yearly performance (2500 km). Private cars achieved a total road performance of 13400 km per year in 2002. difu
Keywords: Verkehr; Straßenverkehr; Entwicklungstendenz; Verkehrsentwicklung; Verkehrsinfrastruktur; Kraftfahrzeug; Personenkraftwagen; Datenerhebung; Statistikmethode; Verkehrsstatistik; Vergleich; Fahrleistung; Jahresfahrleistung; Zuwachsrate